Surface structures of sodium borosilicate glasses from molecular dynamics simulations. Issue 6 (20th March 2017) - Ren, Mengguo; Deng, Lu; Du, Jincheng
Abstract: Surface plays an important role in the physical and chemical properties of oxide glasses and controls the interactions of these glasses with the environment, thus dominating properties such as the chemical durability and bioactivity. The surface atomic structures of a series of sodium borosilicate glasses were studied using classical molecular dynamics simulations with recently developed compositional dependent partial charge potentials. The surface structural features and defect speciation were characterized and compared with the bulk glasses with the same composition. Our simulation results show that the borosilicate glass surfaces have significantly different chemical compositions and structures as compared to the bulk. The glass surfaces are found to be sodium enriched and behave like borosilicate glasses with higher R (Na2 O/B2 O3 ) values. As a result of this composition and associated structure changes, the amount of fourfold boron decreases at the surface and the network connectivity on the surface decreases. In addition to composition variation and local structure environment change, defects such as two‐membered rings and three‐coordinated silicon were also observed on the surface. These unusual surface composition and structure features are expected to significantly impact the chemical and physical properties and the interactions with the environments of sodium borosilicate glasses.